2021
DOI: 10.1111/bjh.17920
|View full text |Cite
|
Sign up to set email alerts
|

An update on the US adult thalassaemia population: a report from the CDC thalassaemia treatment centres

Abstract: Thalassaemia is caused by genetic globin defects leading to anaemia, transfusion-dependence and comorbidities. Reduced survival and systemic organ disease affect transfusion-dependent thalassaemia major and thalassaemia intermedia. Recent improvements in clinical management have reduced thalassaemia mortality. The therapeutic landscape of thalassaemia may soon include gene therapies as functional cures. An analysis of the adult US thalassaemia population has not been performed since the Thalassemia Clinical Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Finally, even in countries associated with advanced health care systems, comorbidities, and even mortality, are increased in transfusion-dependent thalassaemia. 3,4 For these reasons, given the same starting conditions, patients will be treated differently according to the country and institution they are in. Therefore, in this review I have tasked experts from around the world to describe their management plan and rationale for a specific disease presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, even in countries associated with advanced health care systems, comorbidities, and even mortality, are increased in transfusion-dependent thalassaemia. 3,4 For these reasons, given the same starting conditions, patients will be treated differently according to the country and institution they are in. Therefore, in this review I have tasked experts from around the world to describe their management plan and rationale for a specific disease presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated transfusions or inappropriate digestive hyperabsorption of iron caused by an impaired hepcidine‐erythroferone axis result in progressive iron overload. Long‐term effects of iron overload include myocardial dysfunction, liver failure and endocrine dysfunction, which all greatly influence the prognosis and burden of β‐thalassemia 3–5 . While iron chelation therapy is generally mandatory to control iron overload, few disease‐modifying treatments are available to reduce transfusion requirements 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Long-term effects of iron overload include myocardial dysfunction, liver failure and endocrine dysfunction, which all greatly influence the prognosis and burden of β-thalassemia. [3][4][5] While iron chelation therapy is generally mandatory to control iron overload, few disease-modifying treatments are available to reduce transfusion requirements. 6 Hydroxycarbamide, an HbF inducer, may reduce the need for transfusions in subgroups of patients, while more recent drugs such as luspatercept or mitavopivat may further show some benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, combined chelating agents and heart failure management have been recognized as management strategies of TDT alongside regular lifelong blood transfusion. Clinical trials on iron chelators and their combination regimens have been well described in a review article by Chapin J et al [12]. However, a recently pub-lished study curating national thalassemia registry data has indicated that iron chelator agents are not evenly accessible for all TDT patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials on iron chelators and their combination regimens have been well described in a review article by Chapin J et al [12]. However, a recently pub-lished study curating national thalassemia registry data has indicated that iron chelator agents are not evenly accessible for all TDT patients [12]. Younger TDT patients are likely to be prescribed combination iron chelators, yet they exhibited significantly higher mean serum ferritin concentration during a 12-month interval period of observation.…”
Section: Introductionmentioning
confidence: 99%